2022
DOI: 10.3390/su142114380
|View full text |Cite
|
Sign up to set email alerts
|

Different Interspecies Demographic Histories within the Same Locality: A Case Study of Sea Cucumbers, Cuttlefish and Clams in Greek Waters

Abstract: Coalescent methods in population genetics aim to detect biodiversity patterns, evolutionary mechanisms, and signatures of historical changes in effective population sizes with respect to the species fidelity. Restriction site-associated DNA sequencing (RADseq) was used to evaluate the population dynamics of invertebrate species within the same localities. New sequencing technologies, such as the ones employed by population genetics, could be used to improve the management and sustainability of marine and aquac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…The high genetic diversity within each A. Aerophoba population contrasts with the high endemism index generally observed in Mediterranean sponge populations (Coll et al, 2010). This pattern of population differentiation between the eastern and western basin (Feidantsis et al, 2022;Pansini et al, 2003;), is also observed in other sponges such as Petrosia ficiformis (Riesgo et al, 2019), while in others such as the commercial Spongia officinalis shows minimal genetic flow (Νm) (Dallianis et al, 2011).…”
Section: Discussion -Conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…The high genetic diversity within each A. Aerophoba population contrasts with the high endemism index generally observed in Mediterranean sponge populations (Coll et al, 2010). This pattern of population differentiation between the eastern and western basin (Feidantsis et al, 2022;Pansini et al, 2003;), is also observed in other sponges such as Petrosia ficiformis (Riesgo et al, 2019), while in others such as the commercial Spongia officinalis shows minimal genetic flow (Νm) (Dallianis et al, 2011).…”
Section: Discussion -Conclusionmentioning
confidence: 94%
“…These environmental changes probably led to different evolutionary forces in the population dynamics of the species (Petit, 2003), and therefore speciation or even bottleneck effect phenomena may drove in species-specific population shrinks (Riesgo et al, 2016). The most important period was during the Pleistocene glaciations (Hewit et al, 2000), where barriers to gene flow and isolated refugia were created (Moura et al, 2014;Feidantsis et al, 2022;Konstantinidis et al, 2022). The later has been argued that, within the Mediterranean Sea various marine organisms show a differentiation pattern between the eastern and the western basin (Moura et al, 2013;Gkafas et al, 2017;Trajer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous molecular studies of H. tubulosa show a rather strong genetic differentiation between semi-enclosed areas in the eastern Mediterranean [32]. Signatures of historical population demography show a bottleneck event for the species approximately after the Last Glacial Maximum (LGM), revealing a massive loss of genetic diversity, followed by a more recent recovery of the population in the area.…”
Section: Introductionmentioning
confidence: 96%